Analisis dan Perancangan E-Commerce Mitra Dolanan Store Guna Meningkatkan Layanan Penjualan dengan Metode Extreme Programming - Nabilla Agustina Nabilla (LPPM Universitas Merdeka Madiun, 2022)
Mitra Dolanan Store is a company engaged in the retail of children's toys. However, the shop is still not supported with good facilities. As in the case of data processing goods and customers still use a system that is less efficient. Likewise in the marketing system in this store, they still do offline marketing by making banners and posters that are installed in front of the store. In this study, the method used in system design is the Extreme Programming method. The Extreme Programming method has the first stage of planning (Planning), then the second is designing (Design), then the third is coding (Coding), and finally the fourth is testing (Testing). These problems must be supported by implementing a system with structured and computerized functions in sales and purchases which is expected to assist shop owners in increasing their business activities. So we need an E-Commerce on a website-based Dolanan Store Partner. Through this web application, it can help Dolanan Store Partners eliminate competition between sellers and can be a special attraction for customers while helping to increase sales profits.